A Retrospective 05 Years Analysis of Operated Surgical Patients in Bangladesh Level II Hospital, UNMIL - Uddin, MB; Ahmed, MU; Haque, MA; Hussain, MD; Hossain, SME (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: There is a paucity of published data on the type of surgical conditions that affect the UN personnel of different countries setup and the spectrum of surgical operations performed for these patients. Such information are necessary for assessing the impact of surgical conditions, both elective and emergency, on the health of UN peacekeepers from different races and nationalities and for setting priority to improve the surgical care. Objectives: To ascertain highest possible standard of surgical care to be ensured in an international arena for optimal outcome. Materials and methods: Five years retrospective study was carried out in Bangladesh level II hospital (BANMED), UNMIL located at Suakoko district of Liberia from April 2007 to April 2012 comprising of all major and minor surgical cases with different types of dressings done. Results: A total 83 major, 567 minor and 3924 dressings were done. The majority of operations were emergency cases of which 73.49% were of major and 78.30% were minor surgery. While 26.50% of major and 21.69% of minor surgery were elective cases. All were male patients in cases of major operations and 93.29% for minor cases as most of the peacekeepers were male personnel. The most frequent cases were acute appendicitis, inguinal hernia and polytrauma cases. Highest number of patients was 28 (33.73%) from 26-30 years age group. There were 3 minor postoperative complications with nil mortality rates. Conclusion: The surgical unit of a level-II hospital has to work in an adverse situation of a conflict area with various limitations. So it is very important to provide highest possible standard of surgical care to be ensured in terms of staff, equipments, logistic support and with a motivated surgical team in an international arena for optimal outcome. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18720 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 14-19